Morphological and immunohistochemical peculiarities of oncomarkers in placental barrier - T.D. Zadorozhnaya; V.V. Podolsky; O.I. Eshchenko; T.N. Archakova; S.M. Kilikhevich; O.I. Parnitskaya; Yu.V. Davydova; A.A. Grebinichenko; E.A. Pasechnik (Zaporozhye State Medical University, 2012)
Histological and electron microscopy investigations in 47% cases showed disorders of microcirculation with haemorrage and excessive deposits of extravillous fi brinoid with presence of pycnosis and nucleus polymorphism. In 1st investigation group in I pregnancy trimester in placental barrier structures there were pronounced expression of proliferative marker (Ki-67), protein p53 and decrease of these markers in III trimester that is proved by indexes of proliferation and it is caused by regulating infl uence of these factors on the processes of growth, development, differentiation and cell death in placental barrier structures in pregnancy course. In 2nd group pronounced Ki-67 expression in noted in cytotrophoblast nuclei and less pronounced - in stromal cells and endothelium of vesels that is confi rmed by signifi cant increase of proliferative index. Expression of protein 53 was focal in nuclei of extravilleus trophoblast as compared with negative one in control group. It was noted that oncofetal antigen in 1st group showed trace reaction in cytotrophoblast in early terms of gestation (I trimester) and it was not determined in III trimester of pregnancy. In 2nd group in III trimester pronounced immunoreactivity of oncofetal antigen in cytoplasm of stroma cellular elements (Hofbauer cells, fi broblasts) was noted. Pronounced expression of fundamental marker of cell differentiation of cytokeratin in cyto- and syncytiotrophoblast in pregnancy course shows that differentiation processes in placental barrier take place before term labor.